Beatrice Barefacts - Herbert, Victor, 1859-1924 (New York : M. Witmark & Sons, 1904)
For 2 voices and piano; excerpt from the musical It happened in Nordland (later interpolated into Babes in Toyland); accompaniment originally for orchestra